Food Choices: Social Factors and Cultural Capital Affecting Food Choices: A Case Study of Undergraduate Students, Bangkok - Kamkoon, Supasit; Sindecharak, Teera (Thammasat Journal, 2026)
This study aimed to investigate the food choices of undergraduate students in Bangkok and to analyze the influence of social factors and cultural capital on the food choices of undergraduate students. This quantitative cross-sectional study involved undergraduate students. The sample size was 472 participants. A questionnaire, developed based on the concepts of food choices, life course, social and environmental influences, and cultural capital, was used for data collection. The collected data were analyzed using descriptive and inferential statistics, focusing on multiple linear regression. The findings revealed that the most significant factors influencing students’ food choices were ethical concerns, mood, and price. Social factors: income level was positively correlated with all dimensions of food choice (p < .05), and the level of education was significantly associated with health (p = .005). The institution influenced the natural ingredients (p = .023), and the residence was related to price (p = .023). The life course about time constraints were correlated with health (p = .002) and the physical environment was linked to multiple dimensions. The embodied cultural capital about cooking skills was correlated with all food choices (p < .05), and institutionalized cultural capital showed a significant association with convenience and weight control (p < .05). In conclusion, this study highlights the influence of social factors and cultural capital on the food decision-making of students, providing information for agencies to develop strategies to promote appropriate consumption.